Finnish student teachers' perceptions on the role of purpose in teaching. Issue 5 (19th October 2016) - Tirri, Kirsi; Kuusisto, Elina
Abstract: This study identifies the nature of the purposes that Finnish student teachers of different subjects ( N = 372) have for teaching and how these perceptions could inform teacher education. Earlier studies have shown that both American and Finnish students have found the role of their teachers to be very important in teaching and learning purpose. Finnish student teachers have also been found to be purposeful in their teaching. The data for this study were gathered in 2013 with quantitative questionnaires measuring different elements of purpose, such as purpose identification, goal-directedness, beyond-the-self orientation, and competence to teach purpose. Using K-Cluster analysis, four purpose profiles were identified among student teachers: Purposeful, Dabblers, Dreamers, and Disengaged. Student teachers of religious education were found to be the most purposeful in their profiles, while student teachers of mathematics differed from the others, with more than 40% having a Disengaged profile. The results indicate that student teachers of mathematics need special support for their purpose development, as well as education in purposeful teaching.